Problematika Perkawinan Beda Agama Menurut Uu No.1 Tahun 1974 - Anna Liwa, Maria; Titin Roswitha Nursanthy, Aji; Japri, Muhammad (Collegium Studiosum Journal, 2018)
Law No. 1 of 1974 concerning Marriage in Article 2 paragraph (1): Marriage is legal if it is carried out according to the law of each religion and belief. Means the Marriage Law No. 1 of 1974 has not yet confirmed the regulation of interfaith marriages. The tendency to close, make it difficult, or obscure the implementation of community aspirations for interfaith marriage is considered by some to be contrary to the Marriage Law No. 1 of 1974. In Article 6 paragraph (1) of the Marriage Law no. 1 of 1974 states "Marriage is based on the agreement of the two prospective brides" The firmness which states that the basis of marriage is the agreement of the bride and groom, can be interpreted as a form of respect for Human Rights (HAM) based on human dignity. The author uses a normative juridical approach, because of his approach, this model of legal research is called normative legal research.